Comparative Efficacy of Different Drugs for the Treatment of Dilated Cardiomyopathy: A Systematic Review and Network Meta-analysis - Xinyu Tong; Lijuan Shen; Xiaomin Zhou; Yudan Wang; Sheng Chang; Shu Lu (Adis, Springer Healthcare, 2023)
Abstract Background and Objective At present, the therapies of dilated cardiomyopathy concentrated on the symptoms of heart failure and related complications. The study is to evaluate the clinical efficacy of a combination of various conventional and adjuvant drugs in treating dilated cardiomyopathy via network meta-analysis. Methods The study was reported according to the PRISMA 2020 statement. From inception through 27 June 2022, the PubMed, Embase, Cochrane library, and Web of Science databases were searched for randomized controlled trials on medicines for treating dilated cardiomyopathy. The quality of the included studies was evaluated according to the Cochrane risk of bias assessment. R4.1.3 and Revman5.3 software were used for analysis. Results There were 52 randomized controlled trials in this study, with a total of 25 medications and a sample size of 3048 cases. The network meta-analysis found that carvedilol, verapamil, and trimetazidine were the top three medicines for improving left ventricular ejection fraction (LVEF). Ivabradine, bucindolol, and verapamil were the top 3 drugs for improving left ventricular end-diastolic dimension (LVEDD). Ivabradine, l-thyroxine, and atorvastatin were the top 3 drugs for improving left ventricular end-systolic dimension (LVESD). Trimetazidine, pentoxifylline, and bucindolol were the top 3 drugs for improving the New York Heart Association classification (NYHA) cardiac function score. Ivabradine, carvedilol, and bucindolol were the top 3 drugs for reducing heart rate (HR). Conclusion A combination of different medications and conventional therapy may increase the clinical effectiveness of treating dilated cardiomyopathy. Beta-blockers, especially carvedilol, can improve ventricular remodeling, cardiac function, and clinical efficacy in patients with dilated cardiomyopathy (DCM). Hence, they can be used if patients tolerate them. If LVEF and HR do not meet the standard, ivabradine can also be used in combination with other treatments. However, since the quality and number of studies in our research were limited, large sample size, multi-center, and high-quality randomized controlled trials are required to corroborate our findings.